KORELASI SPECIAL EVENT DAY TANGGAL KEMBAR TERHADAP MINAT BELI MASYARAKAT DI SHOPEE - Lisda Tawasuli; Kholifah Kholifah (LP3M Universitas Putra Bangsa, 2023)
Certain promo programs can be carried out as an effort to boost sales. One of the promo programs carried out by Shopee is a special event day which is held on twin dates. This special event day is held routinely every month on twin dates. Shopee provides the most promotional offers on special event days. The method used in this study is a quantitative method with the instrument used in the form of a Likert scale model questionnaire. The questionnaire containing questions is intended for all people who actively transact using Shopee. From distributing the questionnaire questions, 30 respondents were obtained as a population with a sample test that the researchers did to analyze the data using SPSS. Based on data processing and from the results of the analysis obtained in this study, it can be concluded that there is a moderate positive correlation between the Special Event Day of Twin Dates and people's purchasing power at Shopee. The majority of 30 respondents use the shopee application to transact more than 5 times a month, showing that there is a relationship between Special Event Days on twin dates and people's buying interest in shopee as well as shown by the results of a significance value of 0.000 which is smaller than 0.05. which is the standard value of the correlation of a variable in the SPSS software and the Pearson correlation value of 0.833 which shows the degree of correlation is very strong and the form of the relationship between the two variables is positive.